PERSPECTIVAS DOCENTES SOBRE ESTUDANTES DE ORIGEM BOLIVIANA NA REDE PÚBLICA MUNICIPAL DE ENSINO DE CORUMBÁ/MS: DESAFIOS EDUCACIONAIS NA FRONTEIRA BRASIL-BOLÍVIA - Daniella Ibarreche de Menezes (2024)
This dissertation explores the perception of teachers from the municipal public school system of Corumbá about the reality of students of Bolivian origin in the educational institutions of the municipality. The field research was carried out in a school in the upper part of the municipal urban area, with a growing population from Bolivia. The general objective is to analyze the reality of the student of Bolivian origin in the municipal education institutions of the municipality of Corumbá, and specific objectives, to identify the challenges faced by these students and to provide opportunities for the strengthening of actions to improve the reception and relationships in the school environment. . As one of its methodological procedures, a survey was carried out of research already developed by graduates of the Master's Degree in Border Studies in the municipal educational sphere, to dimension the existing studies with this theme, in addition to reflections on the productions of authors such as Álvaro Vieira Pinto and Pierre Bordieu, making a correspondence with the context of schools located in border regions. This research has a qualitative approach, seeking understanding from the perspective of the participants and the context in which they occur. As a data collection technique, semi-structured interviews were used with teachers who work in Early Childhood Education at the researched school. According to the results achieved in the interviews, it was perceived that the lack of support from schools and adequate training to work in schools located on a border directly affects the reality of students of Bolivian origin. Keywords: Education. Border. Students of Bolivian Origin.